Irinotecan Plus S-1 Followed by Hepatectomy for a Patient with Initially Unresectable Colorectal Liver Metastases, Who Showed Severe Drug Rash with Oxaliplatin Plus 5-FU and Leucovorin (FOLFOX) - Hiroyuki Komori; Toru Beppu; Yasuo Sakamoto; Yuji Miyamoto; Hiromitsu Hayashi; Katsunori Imai; Hidetoshi Nitta; Masayuki Watanabe; Hideo Baba (Case Reports in Gastrointestinal Medicine)
For unresectable colorectal liver metastases (CRLM), hepatic resection with or without chemotherapy is the only curative treatment that sufficiently achieves long-term survival. However, occasional severe allergic responses to anticancer drugs necessitate treatment discontinuation. A 45-year-old woman presented with metachronous unresectable colorectal liver metastases. Chemotherapy with oxaliplatin plus 5-FU and leucovorin (FOLFOX) was initiated, but severe allergic dermatitis developed after the second cycle. Although she reported no prior history of adverse reactions to tegafur-uracil, a drug lymphocyte stimulation test showed an allergic response to 5-FU. We subsequently replaced with Irinotecan plus S-1 (IRIS) chemotherapy which was well tolerated and resulted in a partial response after 3 cycles. As a result, right trisectionectomy was successfully performed and no recurrence was detected in the following 3 years. A severe allergic reaction to intravenous 5-FU-containing drug regimens can be successfully alleviated by switching to S-1-containing regimens such as IRIS or S-1 plus oxaliplatin (SOX).